2017
DOI: 10.1007/s10549-017-4160-5
|View full text |Cite
|
Sign up to set email alerts
|

High PTEN gene expression is a negative prognostic marker in human primary breast cancers with preserved p53 function

Abstract: PurposePTEN is an important tumor suppressor in breast cancer. Here, we examined the prognostic and predictive value of PTEN and PTEN pseudogene (PTENP1) gene expression in patients with locally advanced breast cancer given neoadjuvant chemotherapy.MethodsThe association between pretreatment PTEN and PTENP1 gene expression, response to neoadjuvant chemotherapy, and recurrence-free and disease-specific survival was assessed in 364 patients with locally advanced breast cancer given doxorubicin, 5-fluorouracil/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Upregulated PTENP1 was associated with significantly higher PTEN gene expression and PTEN protein levels, thus indicating close coregulation of PTEN and PTENP1 mRNA levels. Although these data are consistent with those in our recent publication demonstrating a significant correlation between PTEN and PTENP1 gene expression in 317 locally advanced breast cancers, that clinical study has found no association between PTENP1 mRNA and PTEN protein levels (7). In line with these findings, upregulated PTENP1 3 0 UTR did not influence PTEN protein expression in either of the breast cancer xenograft models assessed in the current work.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Upregulated PTENP1 was associated with significantly higher PTEN gene expression and PTEN protein levels, thus indicating close coregulation of PTEN and PTENP1 mRNA levels. Although these data are consistent with those in our recent publication demonstrating a significant correlation between PTEN and PTENP1 gene expression in 317 locally advanced breast cancers, that clinical study has found no association between PTENP1 mRNA and PTEN protein levels (7). In line with these findings, upregulated PTENP1 3 0 UTR did not influence PTEN protein expression in either of the breast cancer xenograft models assessed in the current work.…”
Section: Discussionsupporting
confidence: 94%
“…In line with these findings, upregulated PTENP1 3 0 UTR did not influence PTEN protein expression in either of the breast cancer xenograft models assessed in the current work. Whereas PTEN has been examined by IHC in our previous clinical study (7) and was examined by Western blotting herein, PTEN protein analysis was performed by reverse-phase protein array in the TCGA dataset, thus potentially explaining the lack of correlation between PTENP1 gene expression and PTEN protein levels that we observed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding is related to our previous observation in a different cohort of patients treated in the pre-trastuzumab era (16), where PIK3CA mutation types interacted with PTEN status and affected outcome in opposite directions. Further in breast cancer, TP53 mutation status may influence the prognostic CANCER GENOMICS & PROTEOMICS 16: 195-206 (2019) 202 effect of PIK3CA mutations (25) and of preserved PTEN (34), while the unfavourable effect of PTEN-loss may be augmented in the presence of additional alterations interfering with the activation of the PI3K pathway (35). All this argumentation suggests that we need to shift our view from single oncogenic drivers to a molecular environment that certainly interferes with-and may alter the effects of these drivers (36).…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR has been proposed as predictive marker for metastatic progression and overall survival in early-stage tumors of breast cancer (Gupta et al, 2010). On the other hand, NEAT1 and PTENP1, commonly known as tumor suppressors in various cancer types, have been shown to potentiate cell growth and tumor progression in breast cancer (Ke et al, 2016;Yndestad et al, 2017;Yndestad et al, 2018). Collectively, these nuances emphasize the tissue/ cell specificity of lncRNAs and their ability to selectively target genes and impact signaling cascades in a confined manner.…”
Section: Introductionmentioning
confidence: 99%